FACTORS AFFECTING THE INCOME OF SEAWEED FARMERS IN SIDENRE KELURAHAN, BINAMU DISTRICT, JENEPONTO REGENCY - Jam'an, Jam'an; Syahriani, A. Tenri; Nurliah, Nurliah (Perpustakaan dan Penerbitan Unismuh Makassar, 2019)
This study aims to (1) determine the effect of working capital on the income of seaweed farmers in Jeneponto Regency, (2) determine the effect of land area on the income of seaweed farmers in Jeneponto Regency, (3) determine the effect of production on the income of seaweed farmers in Jeneponto Regency, (4) to determine the effect of the selling price on the income of seaweed farmers in Jeneponto Regency. This research was conducted in Jeneponto Regency to be precise Sidenre Village. This research uses quantitative research. This study covers the factors that affect the income of seaweed farmers in Jeneponto Regency with the variables used, namely working capital, land area, production and selling price. The results of this study indicate that the working capital variable has a positive and significant effect on the income of seaweed farmers in Jeneponto district, the variable land area has a positive and significant effect on the income of seaweed farmers in Jeneponto district, the production variable has a positive and significant effect on the income of seaweed farmers in the district. Jeneponto and the selling price variable have a positive and significant effect on the income of seaweed farmers in Jeneponto district.